2020
DOI: 10.1152/japplphysiol.00137.2019
|View full text |Cite
|
Sign up to set email alerts
|

Aging reduces cerebral blood flow regulation following an acute hypertensive stimulus

Abstract: Reductions in cerebral blood flow and increases in flow pulsatility with aging are associated to cerebrovascular disease; however, little is known about how an acute hypertensive stimulus effects cerebral blood flow regulation in an aged population. Following the hypertensive stimulus, older adults elicit an attenuated increase in cerebral blood velocity and greater transmission of pulsatile velocity to the brain compared with young adults, demonstrating reduced cerebral blood flow regulation to elevated blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…This is in line with the findings of De Heus et al ( 2018 ), who reported a lower (better) %MCAv response for a given change in blood pressure in MCI compared to control, which is suggestive of maintained cerebral autoregulation in MCI. Our group (Klein et al 2020 ) and others (Rosenberg et al 2020 ) have recently suggested that higher arterial stiffness leads to the greater transmission of pulsatile blood velocity in healthy older adults. We observed that higher pressure-responsiveness in the control group was positively associated with systemic pressure augmentation (AIx) in this study.…”
Section: Discussionmentioning
confidence: 78%
“…This is in line with the findings of De Heus et al ( 2018 ), who reported a lower (better) %MCAv response for a given change in blood pressure in MCI compared to control, which is suggestive of maintained cerebral autoregulation in MCI. Our group (Klein et al 2020 ) and others (Rosenberg et al 2020 ) have recently suggested that higher arterial stiffness leads to the greater transmission of pulsatile blood velocity in healthy older adults. We observed that higher pressure-responsiveness in the control group was positively associated with systemic pressure augmentation (AIx) in this study.…”
Section: Discussionmentioning
confidence: 78%
“…Vessel reactivity, assessed by CO 2 ‐challenge in MRI and positron emission tomography (PET), shows widespread age‐related reduction (Ito et al., 2001; Lu et al., 2011). These in vivo findings are supported by histological observations that aging is associated with vascular stiffness, necrosis of vascular smooth muscle, thickening of basement membrane, venous collagenosis, increased tortuosity and “blind‐ends” in vessel morphometry, providing microscopic evidence that vessel reactivity declines with aging (Fabiani, Low, et al., 2014; Fang, 1976; Rosenberg et al, 2020; see Abdelkarim et al., 2019; D'Esposito et al., 2003; Tsvetanov et al., 2021; for reviews).…”
Section: Current Neurocognitive Aging Theories and Their Predictionsmentioning
confidence: 72%
“…For instance, long-term, 1 m/s increase in cfPWV is associated with a 14-15% increase in cardiovascular events (Vlachopoulos et al, 2010). Acutely, among older adults with and without hypertension, transiently increased cfPWV is associated with cerebrovascular pulsatility (Lefferts et al, 2018;Rosenberg et al, 2020) and end-organ damage (Keith et al, 2013) following an acute bout of aerobic exercise. Prolonged exposure to elevated cfPWV may transmit pulsatile flow to the cerebrovasculature and increase the risk of cerebrovascular events in aging populations (Rosenberg et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Acutely, among older adults with and without hypertension, transiently increased cfPWV is associated with cerebrovascular pulsatility (Lefferts et al, 2018;Rosenberg et al, 2020) and end-organ damage (Keith et al, 2013) following an acute bout of aerobic exercise. Prolonged exposure to elevated cfPWV may transmit pulsatile flow to the cerebrovasculature and increase the risk of cerebrovascular events in aging populations (Rosenberg et al, 2020). It is possible that individuals with preexisting cardiovascular risk factors may be sensitive to sustained elevations in pulsatility through arterial stiffness acutely after exercise.…”
Section: Discussionmentioning
confidence: 99%